2016
DOI: 10.1542/peds.2015-2238
|View full text |Cite
|
Sign up to set email alerts
|

Kangaroo Mother Care and Neonatal Outcomes: A Meta-analysis

Abstract: CONTEXT: Kangaroo mother care (KMC) is an intervention aimed at improving outcomes among preterm and low birth weight newborns.OBJECTIVE: Conduct a systematic review and meta-analysis estimating the association between KMC and neonatal outcomes. STUDY SELECTION:We included randomized trials and observational studies through April 2014 examining the relationship between KMC and neonatal outcomes among infants of any birth weight or gestational age. Studies with <10 participants, lack of a comparison group with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
440
3
33

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 486 publications
(496 citation statements)
references
References 134 publications
20
440
3
33
Order By: Relevance
“…After birth, breastfeeding-related problems must be prevented, as they can be a cause of metabolic disorders, including derangements in blood glucose. This could be prevented by strict hypoglycemia prevention protocols [23] or by existing, well-established programs (kangaroo mother care) [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After birth, breastfeeding-related problems must be prevented, as they can be a cause of metabolic disorders, including derangements in blood glucose. This could be prevented by strict hypoglycemia prevention protocols [23] or by existing, well-established programs (kangaroo mother care) [24].…”
Section: Discussionmentioning
confidence: 99%
“…The wording of questionnaire items was guided by keywords selected on the basis of the recent literature on the topic. Multiple-choice questions were also based on the literature [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: The Second Part Of the Questionnaire Was Subdivided Into Twomentioning
confidence: 99%
“…It has been reported that, thanks to kangaroo care, early initiation and promotion of mother-infant attachment makes the adaptation between mother and infant easier [9]. Kangaroo care means putting the naked baby with a diaper on its mother's or father's bare chest in a face-to-face upright position to establish skin-to-skin contact [6,10]. The name kangaroo care was inspired by the way a mother kangaroo holds her baby in her pouch.…”
Section: Introductionmentioning
confidence: 99%
“…Kangaroo care was initiated by Dr. Edger Rey Sanabria in Bogotá, Colombia in 1978, because neonatal intensive care units were too crowded and resources were inadequate, although rates of mortality and morbidity were high for babies with very low birth weights [6,10]. It is a current issue that kangaroo care should be considered very important due to its low cost, ease of application and positive effects on premature infants (Head 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation